Lipid nephrotoxicity mediated by HIF-1α activation accelerates tubular injury in diabetic nephropathy - Zebo Hu; Qianwen Zhu; Ying Wang; Xue Deng; Hui Yang; Mingjun Zhou; Jiyuan Zhang; Hao Wang; Haosen Wang; Lin Wang; Cui Zhang; Shu Li (Renal Failure)
This study is intended to explore the effect of hypoxia-inducible factor-1α (HIF-1α) activation on lipid accumulation in the diabetic kidney. A type 1 diabetic rat model was established by STZ intraperitoneal injection. Cobalt chloride (CoCl2) and YC-1 were used as the HIF-1α activator and antagonist, respectively. CoCl2 treatment significantly increased HIF-1α expression, accelerated lipid deposition, and accelerated tubular injury in diabetic kidneys. In vitro, CoCl2 effectively stabilized HIF-1α and increased its transportation from the cytoplasm to the nucleus, which was accompanied by significantly increased lipid accumulation in HK-2 cells. Furthermore, results obtained in vivo showed that HIF-1α protein expression in the renal tubules of diabetic rats was significantly downregulated by YC-1 treatment. Meanwhile, lipid accumulation in the tubules of the DM + YC-1 group was markedly decreased in comparison to the DM + DMSO group. Accordingly, PAS staining revealed that the pathological injury caused to the tubular epithelial cells was alleviated by YC-1 treatment. Furthermore, the blood glucose level, urine albumin creatinine ratio, and NAG creatinine ratio in the DM + YC-1 group were significantly decreased compared to the DM + DMSO group. Moreover, the protein expression levels of transforming growth factor β1 (TGF-β1) and connective tissue growth factor (CTGF) in diabetic kidneys were decreased by YC-1 treatment. Our findings demonstrate that the activation of HIF-1α contributed to interstitial injury in a rat model of diabetic nephropathy and that the underlying mechanism involved the induction of lipid accumulation.